Manajemen Kas Berbasis Virtual Account Pada PT PLN (Persero) UPP Pembangkit Jawa Bagian Barat - Tri Wahyudi (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2021)
The company's operational activities can run optimally if cash is managed properly. In the cash of PT PLN (Persero) UPP Pembangkit Jawa Barat there is petty cash which is used to finance the company's operational activities of small value. The purpose of this study was to determine petty cash management based on the virtual account system at PT PLN (Persero) Unit Pelaksana Proyek (UPP) Pembangkit Jawa Bagian Barat so that it could see the cash management process more effectively and efficiently. This research is descriptive in nature, namely research by describing the condition of the company based on actual conditions. From the results of this study, it was found that PT PLN (Persero) Unit Pelaksana Proyek (UPP) Pembangkit Jawa Bagian Barat uses a cash management system with the Imprest system by determining the petty cash value that has been determined per week by PT PLN (Persero) Unit Induk Pembangunan (UIP) Jawa Bagian Barat. Petty cash is taken using an ATM card media which can only be withdrawn for petty cash during working hours and days. Cash management through virtual accounts really helps the cash management process in real time and minimizes idle cash.